Relación entre los procesos de reservas que se generan con dos reclamaciones relacionadas en el tiempo (2014)
For insurance companies the reservation process is the fundamental basis for controlling portfolios contracted to facilitate the manipulation of mathematical and probabilistic model. Sometimes the model is discretized so that the results approximate the real solution in the continuum, in this case the compound binomial model is used for this purpose. In most contexts the assumption of independence is assumed, in this article we consider dependence between two types of complaints referred to the principal claim and over-claim or subsequent claim, the latter will be involved whenever there is a claim principal. The type of model with timerelated claims process generates two reserves, one for when the subsequent claim is not delayed to a next time and another where it covers the total claimed by both the principal and by the subsequent claim. Since manipulate these processes separately is unnecessary and impractical, we generate from the survival probabilities of both processes and manipulate the probability generating functions, an equation that collects information from the two processes of reserves.